Krščanstvo in marksizem - Škamperle, Igor (Poligrafi, 2020)
The article illustrates the concurrences of Christianity and Marxism, expressed in the advocacy of a free man and a just society; and where the two depart: in the conception of the human person and in the understanding of the final destination of a man who remains open in Christianity and thus transfers to eternal love of God. for Marxism, this vision is immanent, confined to the subject world and a just society. The two views come into conflict because both act as religions; and Christianity is primarily about human beings, and Marxism inculcates the whole world.
Keywords: krščanstvo; marksizem; religija